Supportive beliefs: why should teachers understand their nature and role? - Bambirra, Maria Raquel (2012)
Assuming the demands of educating teachers for classroom practice, it is high time researchers investigated beliefs in action deeper. Rokeach’s (1968) concepts of central and peripheral values as gradient for discussing and defining the nature of beliefs, among the contribution of others, have provided Applied Linguistics with a gateway to study the dynamics of belief change. Framed by these studies and the results of a doctoral study on autonomy development, this paper aims at acknowledging a third element into the gradient: supportive beliefs, which for their content, nature and role in human cognition refer to beliefs that cannot be considered peripheral. We present evidence that some currently considered peripheral beliefs are, in fact, supportive beliefs, whose existence protects central beliefs from being banned from cognition whenever challenged. Data to support such claim were collected from a written narrative and a series of five interviews with a 45 year-old woman, taking an intermediate level English course in Brazil, as part of a larger case study. During the interviews, some of this woman’s beliefs were challenged. We discuss how she defended, maintained, modified or totally discarded them and refer to the difficulty of changing beliefs due to their emotional and/or cognitive relevance.